Inflation announcements, federal reserve bias and stock returns - Coelho, Miguel (2010)
In this article, we found that the US stock prices react only to the unexpected component of US inflation announcements, with such impact statistically significant only in a situation of economic recession. We also show that the impact of the unexpected component of inflation announcements is also dependent upon the "signals" that the Federal Reserve sends to the market (the known Federal Reserve Bias). In fact, we found a negative correlation between the unexpected component of macroeconomic announcements and stock price returns, this correlation being statistically significant when the Federal Reserve discloses a Neutral Bias.